Job Creation and Destruction: New Evidence on the Role of Small Versus Young Firms in Korea. (5th December 2016) - Cho, Janghee; Chun, Hyunbae; Kim, Hongjun; Lee, Yoonsoo
Abstract : Using the Census on Establishments data in Korea, the present study revisits the role of firm age and size to explain aggregate employment dynamics. We confirm the finding of Haltiwanger et al . that no systematic inverse relationship exists between net job growth and firm size once firm age is controlled for. We find that small businesses are driving forces of aggregate employment growth but that such high growth is mostly driven by the entry of very small firms, which is offset by job destructions of a similar magnitude. Moreover, entrepreneurial activity occurs among very small firms, whereas large start‐ups are rarely observed.